Analisis Konsumsi Air Sayuran Organik dalam Rumah Tanaman - Vita Ayu Kusuma Dewi; Budi Indra Setiawan; Roh Santoso Budi Waspodo (Jurnal Irigasi, 2017)
Organic vegetables grown special in planthouses require  special irrigation practice to maintain  the optimum range of soil water content throughout the cultivation season. The problem of irrigation is the absence of parameter that used to determine schedule and water irrigation. This research was to figure out whether the sprinkle irrigation used for Kailan vegetable in a planthouse could fulfil the water demand and the total water consumption based on change of water content. Herewith, the daily soil moisture was observed and analyzed the water flow in the soil based on the soil physical and hydraulic properties. The result showed that the soil water content  was always within field capacity and permanent wilting point but 87% of cultivation period was lower than readily avaiable water (RAW). This condition indicated that the water irrigation is not optimal. Based on change of soil water content analysis, water consumption for kailan was 55  mm during cultivation with  the consumption rate was 1.1 mm/day. The water requirement to attain RAW condition was 130 mm.